2020
DOI: 10.1590/0103-644020200
|View full text |Cite
|
Sign up to set email alerts
|

Association between Estrogen, Vitamin D and Microrna17 Gene Polymorphisms and Periapical Lesions

Abstract: This study evaluated the association between polymorphisms in genes encoding estrogen receptors 1 (ESR1) and 2 (ESR2), vitamin D receptor (VDR) and in microRNA17 (which binds to ESR1 and VDR) with persistent apical periodontitis (PAP) after the endodontic treatment. We included 162 patients who completed endodontic treatment at least one year ago and presented apical periodontitis at the beginning of the root canal therapy. Clinical and radiographic exams were performed to evaluate the presence of PAP or healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…28 Accumulating evidence identified various genetic variants within the MIR17HG gene, including (rs4284505; g.91349218A>G), (rs17735387; g.91353800G>T), (rs1428; g.91354516C>A), (rs7336610; g.91352883C>T), and (rs72640333; g.91352673T>A) that are destined to be correlated with different disorders involving multiple myeloma, 13 breast cancer, 4 multiple sclerosis, 21 and periapical lesions. 20 Until now, to the best of our knowledge, this is the first study investigating the association of MIR17HG (rs4284505; A>G) variant with the development of SLE among a sample of Middle Eastern population. Our findings indicated that the A/G genotype revealed a protective effect against the development of SLE, and this protective effect remains significant after stratifying the patients according to the presence of lupus nephritis.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…28 Accumulating evidence identified various genetic variants within the MIR17HG gene, including (rs4284505; g.91349218A>G), (rs17735387; g.91353800G>T), (rs1428; g.91354516C>A), (rs7336610; g.91352883C>T), and (rs72640333; g.91352673T>A) that are destined to be correlated with different disorders involving multiple myeloma, 13 breast cancer, 4 multiple sclerosis, 21 and periapical lesions. 20 Until now, to the best of our knowledge, this is the first study investigating the association of MIR17HG (rs4284505; A>G) variant with the development of SLE among a sample of Middle Eastern population. Our findings indicated that the A/G genotype revealed a protective effect against the development of SLE, and this protective effect remains significant after stratifying the patients according to the presence of lupus nephritis.…”
Section: Discussionmentioning
confidence: 91%
“…miRNAs are large family clusters of tiny noncoding RNAs that are implicated in genomic and epigenomic regulation. 20 The primary function of miRNAs is to target the designated mRNAs causing their instability and/or degradation, mediating their inhibitory effects. 28 Accumulating evidence identified various genetic variants within the MIR17HG gene, including (rs4284505; g.91349218A>G), (rs17735387; g.91353800G>T), (rs1428; g.91354516C>A), (rs7336610; g.91352883C>T), and (rs72640333; g.91352673T>A) that are destined to be correlated with different disorders involving multiple myeloma, 13 breast cancer, 4 multiple sclerosis, 21 and periapical lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations